(3GdMOGFb GdfhQjI aj GdMbGFb GdZhQjIs - (3jMji Hf eMeO GdjROjs
(3ChdgG (B:s
(3GdMeO ddg GdPi edc HcGed SdWGfg QbGH Gdedhc hHYO jbhd GdYHO deG QCjJ HdGO GdYLe eZHQI CQLGhgG JJdGWe CehGL GdeMf JaQbJ LehYgG s
(3BNQgG (B:s
(3HCf Jchf cKQI GdTYQ Ydi GdUOQ CcKjQ ef VYa GdUhJ aMceI Gddg YGdjI Ydi Mce GdBNQI hgPG BNQ eG CQOfGg ai GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs